The Blade runner experience : the legacy of a science fiction classic - Brooker, Will, 1970- (Columbia University Press, 2012)
Since its release in 1982, Ridley Scott's Blade Runner, based on Philip K. Dick's novel Do Androids Dream of Electric Sheep?, has remained a cult classic through its depiction of a futuristic Los Angeles; its complex, enigmatic plot; and its underlying questions about the nature of human identity. The Blade Runner Experience: The Legacy of a Science Fiction Classic examines the film in a broad context, examining its relationship to the original novel, the PC game, the series of sequels, and the many films influenced by its style and themes. It investigates Blade Runner onlin.